Persepsi Kepala Ruangan tentang Hasil Recruitment Perawat Berbasis Kompetensi - Ernita Rante Rupang; Nurmaini Nurmaini; Roymond H. Simamora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study explores the perceptions of the head of the room about the recruitment results of competency-based nurses at Santa Elisabeth Hospital Medan. The research method used is qualitative research with a phenomenological design. The results of this study obtained six main themes, namely: 1) the purpose of recruitment, 2) improvements made in recruitment, 3) obstacles to recruitment implementation, 4) benefits of recruitment, 5) supporting factors for the performance of recruitment, 6) expectations of recruitment results. In conclusion, the head of the room's perception of competency-based nurse recruitment results can help the recruitment team, who is also a part of hospital management, obtain professional and competent nurses according to service needs. Keywords: Competence, Nurse, Recruitment